The I-TAP-PD project and the Greek participation Contribution to local practices of equal collaboration between teachers and artists and to international research - Giannouli, Betty; Choleva, Nassia; Potamousi, Iro (Education & Theatre, 2023)
This paper presents the International Teacher-Artist Partnership – Professional Development (I-TAP-PD) programme, framing the definition and methodology of Teacher- Artist Partnership (TAP) and presenting the structure and content of this programme as implemented by organisations working in the field of education and the arts in 4 countries (Ireland, Serbia, the Netherlands, Greece) in the period between 2020 and 2023. The main characteristics and general research findings from the implementation of the methodology by 6 pairs of artists and teachers in four regions in Greece are then described. The authors outline the steps followed to design, coordinate and implement the international research conducted in the four countries as well as the actions taken so far to disseminate its results.